A Study of Autopsy Findings in Cases of Sudden Cardiac Death at Kakatiya Medical College and Hospital Warangal - Mohd Raza Malik Khan1 , B Shekhar Rao2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background and Objectives: The incidence of sudden cardiac death is increasing in developing countriesdue to changes in lifestyle and food habits. We in the present study tried to evaluate the autopsy findings ofcases of sudden cardiac death reported to Kakatiya Medical College and MGM Hospital Warangal.Methods: The present study was carried in the Department of Forensic Medicine and Toxicology, KakatiyaMedical College and MGM Hospital Warangal from January 2019 to Jan 2020. All the cases including bothsexes those who died suddenly and unexpectedly brought to the institute for post-mortem examination werestudied.Results: In 10% of cases major blockage was noted in both right and left main coronary arteries. Left maintrunk blockage was noted in 31% of cases 5% of cases the blockage was seen in only right coronary arteries.In 32% of cases, the blockage was severe >90%. The highest incidence of major blocks was seen in the agegroup 60-70 years. The younger age group showed the tendency of blockage of the left coronary arteries.The less commonly affected was the circumflex branch and right coronary arteries. MI was the cause ofdeath in 44% of cases and 5% of cases there was evidence of old and fresh infarcts.Conclusion: Within the limitations of the current study it can be concluded that most of the cases of suddencardiac death in this study were from 51-70 years. The most commonly affected victims were males by aratio of 17:3. Autopsy plays an important role in the accurate diagnosis of sudden cardiac death. Thereforemeticulous postmortem examination and histopathological examination are needed to minimize the risk ofnegative reporting